A method for scoring the risk of fungicide resistance in vineyards. (May 2021) - Rossi, Vittorio; Caffi, Tito; Legler, Sara Elisabetta; Fedele, Giorgia
Abstract: Because the risk of resistance towards single-site fungicides in populations of Plasmopara viticola and Erysiphe necator, the causal agents of downy mildew (DM) and powdery mildew (PM), respectively, is substantial, fungicide resistance management is important in vineyards. Available methods for assessing resistance risk mainly focus on single fungicides and do not consider the risk of resistance of a complete fungicide schedule, which typically includes multiple fungicides, used solo or in mixture and at different doses, and other actions (behaviors) of the farmer. A simple scoring method (fungicide resistance risk score, FRRS ) was developed to account for both (i) the intrinsic risk due to the fungicides used, the target pathogens, and agronomic factors, and (ii) the behavioral risk, which includes how the fungicides are used during the season. FRRSs were then calculated for 10 representative vineyards (10 cases) and ranked from 1 (highest score) to 10 (lowest score). For comparison, 20 assessors (four winegrowers and 16 experts including public advisors, field technicians, and consultants) ranked the same cases based on their individual "perception of risk" from 1 (highest risk) to 10 (lowest risk). When the FRRS -based rankings were compared with the modes of the rankings provided by the assessors, the correlation coefficients were significant for all experts (P < 0.001) and for each category of experts (P < 0.05); i.e., public advisors, field technicians from agro-chemical companies, and consultants; for non-experts, i.e., winegrowers, the FFRS values were significantly correlated with the modes of rankings for PM (P < 0.001) but not for DM (P = 0.293). The results indicated that the use of the new scoring method, i.e., the use of FRRSs, would reduce the variability in assessments of resistance risks and would provide a common method for evaluating resistance risk by both experts and winegrowers. Highlights: A fungicide resistance risk score ( FRRS ) for evaluating the risk of fungicide schedules against downy and powdery mildews. FRRSs would reduce the variability in assessments of resistance risks. FRRSs would provide a common method for evaluating resistance risk by both experts and winegrowers.